2017
DOI: 10.1007/s00208-017-1546-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of the squeezing function for a class of bounded domains

Abstract: Abstract. We construct a class of bounded domains, on which the squeezing function is not uniformly bounded from below near a smooth and pseudoconvex boundary point.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…On the other hand, as shown recently in [7], the answer to Question 1 is negative if no other conditions on the bounded domain than the boundary being C 2 are assumed. Also the high dimensions can imply some unexpected phenomenon [6]. Thus the hypothesis of the our theorem is in some sense reasonable.…”
supporting
confidence: 51%
“…On the other hand, as shown recently in [7], the answer to Question 1 is negative if no other conditions on the bounded domain than the boundary being C 2 are assumed. Also the high dimensions can imply some unexpected phenomenon [6]. Thus the hypothesis of the our theorem is in some sense reasonable.…”
supporting
confidence: 51%
“…[21, 11.4, 37.7]). We note that a domain of holomorphy need not be HHR even in finite dimensions, as shown in [8,Theorem 1].…”
Section: Introductionmentioning
confidence: 95%
“…These manifolds possess many important geometric properties (e.g. all classical metrics on them are equivalent) [19,20] and have also been studied by several authors (see, for example, [6,7,8,14,24]) in the case of complex domains. In particular, it has been shown in [24] that a holomorphic homogeneous regular bounded domain D in C n must be pseudoconvex and all strongly convex domains in C n are holomorphic homogeneous regular.…”
Section: Introductionmentioning
confidence: 99%
“…Yeung [8] showed that the answer is yes for strongly convex domains in C n , and Kim-Zhang [6] and Deng-Guan-Zhang [3] showed that the answer is yes for strictly pseudoconvex domains. On the other hand, Fornaess-Rong [4] showed that the answer is no for n ≥ 3.…”
Section: Some Open Problemsmentioning
confidence: 99%
“…For further results about the squeezing function the reader may also consult the references [1], [2], [3], [4], [5], [6], [7], [8], [9]. In the last section we will post some open problems.…”
Section: Introductionmentioning
confidence: 99%